Geopolitične razsežnosti makedonskega narodnega vprašanja - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
GEOPOLITICAL DIMENSIONS OF THE MACEDONIAN NATIONAL QUESTION. Macedonians have a special place among the nations of the Balkan peninsula. Relatively late institutionalization and low number of members, along with the exposed strategic significance of the territory, together with expansion of their neighbours' aggressive ideologies had an unfavourable impact upon the ethnic development of this nation. The article deals with the Macedonian national question in the light of contemporary geopolitical relations, characterized by strongly altered relations of powers in the regional (Balkan) and global context. It is visible at the first sight that the axis of processes lies above all in the strained interethnic relations, which have already escalated into an open conflict in the old Albanian-Serbian and later also Macedonian-Albanian confrontations. However, tensions also exist at the level of Greek-Albanian and Greek-Turkish polarizations, and potentially in Bulgarian_Turkish relations. The system of international interventionism is striving to solve these tensions, having succeeded in preventing direct conflicts, but not to eliminate their reasons. That is why it introduces into the South-Balkan territory the elements of military and political command of the territory. This complex now faces European integrational processes with the concept of the EU expansion, bringing the offer of economic and political stabilization, which function as triggers of economic command of the territory. The latter is of great importance, opening options of economic revitalization and deperriferization of the space. Both approaches are increasing the geostrategic significance of the Macedonian state territory, which is spatially fragmented due to unsuccessful models of regional politics.Yet this in itself doesn't solve any of the Macedonians' existential national problems. On the contrary, it seems to be changing them into a target and object of regional and international forces. In the light of European integrational processes the principles of European geostrategy and geopolicy should be reconsidered as far as the solving of complex relations in the Balkan peninsula and wider is concerned.
Keywords: Makedonija; Republic of Macedonia; evropska integracija; geopolitika; nacionalno vprašanje; etnična struktura; manjšine